Structure integrity analysis on nickel-diamond blade in dicing of hard-brittle ceramic die - S. K., Lim; M. F., Zamri; A. R., Yusoff (Elsevier, 2022)
Dicing operation in cutting hard-brittle ceramic die using nickel-diamond blade causes cracked or chipped die, accelerated tool wear and, ultimately, shortage of blade lifetime. This study aims to analyse the structural integrity of dicing blade in terms of tool wear, surface roughness, microstructure and elements during dicing. The measurements of wear blade on the blade are made by confocal microscope, whereas surface and elemental analyses are carried out with EDX SEM. Results show that the volumetric wear rate of blade is 20%, similar to roughness. The microstructure of the blade changes with occurrence of Aluminium owing to abrasive wear mechanism during cutting.